2018
DOI: 10.1016/s1473-3099(17)30479-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of national and subnational infection prevention and control interventions in high-income and upper-middle-income countries: a systematic review

Abstract: Evidence-based guidance for national infection prevention and control (IPC) programmes is needed to support national and global capacity building to reduce health-care-associated infection and antimicrobial resistance. In this systematic review we investigate evidence on the effectiveness of IPC interventions implemented at national or subnational levels to inform the development of WHO guidelines on the core components of national IPC programmes. We searched CENTRAL, CINAHL, Embase, MEDLINE, and WHO IRIS data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 63 publications
0
38
0
1
Order By: Relevance
“…In Korea, there was a significant decline in device-associated HAI in association with the implementation of the KONIS program [ 17 ]. National IPC programs such as hand hygiene, care bundles, antimicrobial stewardships, and environmental hygiene have been shown to effectively reduce HAI and infections caused by AMR pathogens [ 7 , 18 20 ]. In Taiwan, hand hygiene program over a 4-year period were found to reduce HAI in ICU by 17.2% and BSI by 12.7% [ 20 ], and care bundles to further reduce CAUTI and CLABSI by 22.7 and 12.2%, respectively [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, there was a significant decline in device-associated HAI in association with the implementation of the KONIS program [ 17 ]. National IPC programs such as hand hygiene, care bundles, antimicrobial stewardships, and environmental hygiene have been shown to effectively reduce HAI and infections caused by AMR pathogens [ 7 , 18 20 ]. In Taiwan, hand hygiene program over a 4-year period were found to reduce HAI in ICU by 17.2% and BSI by 12.7% [ 20 ], and care bundles to further reduce CAUTI and CLABSI by 22.7 and 12.2%, respectively [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a general decrease in isolates of important AMR species: MRSA, CRPA and CRAB even though the number of participating ICUs has expanded from 2008 to 2015. This downward trend is likely due to hand hygiene to prevent cross-transmission of AMR pathogens, care bundles to prevent device- or procedure-associated infections, and antimicrobial stewardship programs to mitigate the selection pressure implemented in these countries [ 7 , 18 20 , 29 ]. A recent meta-analysis reported that antimicrobial stewardship programs in Asia reduced overall antimicrobial consumption by 9.74% and incidence density of important AMR pathogens such as MRSA by 0.9 to 1.4 isolates per 1000 patient-days [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In zwei Studien konnte gezeigt werden, dass der Effekt der Surveillance unabhängig von den untersuchten Zeiträumen war [29,30]. Verschiedene systematische Literaturanalysen haben sich mit der wissenschaftlichen Evidenz für einen genuinen, infektionspräventiven Effekt der Surveillance von nosokomialen Infektionen befasst; sie er-lauben zusammengefasst nach der KRIN-KO-Systematik die Zuordnung zur Kategorie IB [31,32]. Kontrollierte Studien zum Effekt der Surveillance wurden seit der SENIC-Studie nicht publiziert.…”
Section: Ziel Der Surveillanceunclassified
“…Conditions for HAIs prevention and control have been considered as a parameter for evaluating health services and reflect the quality of care provided (2) . Insufficiency in these conditions has been a special challenge for low and middle income countries in which HAI rates are even higher (3) .…”
Section: Introductionmentioning
confidence: 99%